2016
DOI: 10.1002/ijc.30373
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor activity of the ATR inhibitor AZD6738 in HER2 positive breast cancer cells

Abstract: Ataxia telangiectasia and Rad3-related (ATR) proteins are sensors of DNA damage, which induces homologous recombination (HR)-dependent repair. ATR is a master regulator of DNA damage repair (DDR), signaling to control DNA replication, DNA repair and apoptosis. Therefore, the ATR pathway might be an attractive target for developing new drugs. This study was designed to investigate the antitumor effects of the ATR inhibitor, AZD6738 and its underlying mechanism in human breast cancer cells. Growth inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…The researchers demonstrated that Rad51 inactivation and γ-H2AX accumulation were more significantly observed after combination treatment. Notably, ATR inhibitor as single agents has been evaluated in HER2-positive breast cancer [24]. The investigators found that AZD6738 reduced several DNA repair proteins and p-AKT levels in sensitive cells but not in insensitive cells.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers demonstrated that Rad51 inactivation and γ-H2AX accumulation were more significantly observed after combination treatment. Notably, ATR inhibitor as single agents has been evaluated in HER2-positive breast cancer [24]. The investigators found that AZD6738 reduced several DNA repair proteins and p-AKT levels in sensitive cells but not in insensitive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent data indicate that the ATR inhibitor AZD6738 is able to penetrate the blood brain barrier, 36 and that ATR knockdown leads to significant sensitization to temozolomide in a glioma cell line. 37 This approach has also been studied in other cancers: ATR inhibition with AZD6738 combined with other therapies proved to be synergistic for pancreatic cancer (ATRi and Gemcitabine), 38 Her2-positive breast cancer (ATRi and Cisplatin), 39 and non-small cell lung cancer (ATRi and Cisplatin). 40 In radiotherapy of glioblastoma, replication stress leading to constitutive activation of the DNA damage response pathway under irradiation is thought to mediate radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Both NF-κB transcription factors and Src proto-oncogene were previously connected with tumorigenesis [67] and breast cancer metastasis [68]. Distant metastasis developed in lymph node negative luminal A patients was associated with cell cycle, DNA repair and immune response mechanisms [69][70][71]. In lymph node positive luminal A patients, distant metastasis was related to mechanisms of T lymphocyte differentiation and activation [72,73] (Figure 2).…”
Section: Molecular Mechanism Associated With Lymph Node and Distant Mmentioning
confidence: 94%